Pembuatan Membran Polimer Elektrolit Berbasis Polistiren Akrilonitril (SAN) untuk Aplikasi Direct Methanol Fuel Cell - Suka, Irwan Ginting; Simanjuntak, Wasinton; Dewi, Eniya Listiani (Jurnal Natur Indonesia, 2010)
In this study, electrolyte membranes based on polystyrene acrylonitrile (SAN) for Direct Methanol Fuel Cell applicationwere prepared. The preparation was carried out in two steps. The first step was introduction of additives, silicaand zeolite, as reinforcing agent on SAN, to obtain silica-reinforced SAN membrane, specified as SAN-Si, andzeolite-reinforced SAN membranae, specified as SAN-Z. The two reinforced membranes were then subjected tosulphonation using sulphuric acid, and the sulphonated membranes are specified as S-SAN-Si and S-SAN-Z,respectively. The characteristics of the membrane were described in terms of the degree of sulphonation, ionicconductivity, methanol permeability, and percentage of swelling in water and methanol. The results obtaineddemonstrated that additives result in significant reduction of methanol crossover, as reflected by lower values ofmethanol permeability than that obtained for the membrane without additive. It was also found that zeolite functionsrelatively better than silica. For zeolite-modified membrane (S-SAN-Z) the ionic conductivity of 10.05 x 10 -6 S/cmwas achieved. The membrane also marked by methanol permeability of 0.52 x 10 -6, percentage of swelling of 5.12%in water and 2.58% in methanol. Thermal analysis using DSC technique revealed changes in glass transition fromthe original sample, in which the glass transition of the original sample, SAN, (55 0C), sulphonated SAN, S-SAN,(83.360C), silica-modified membrane S-SAN-Si (79.860C), and zeolite-modified membrane S-SAN-Z (79.290C). Additionof additive was also found to influence the surface characteristics of the membranes as revealed by SEM analysis,in which the surface changed from smooth for the original sample into rough for the reinforced samples with bothadditives.